Development of efficient path planning algorithm for UAV navigation - Kothai Manickam, Laxman (2018)
In this report, Rapidly-exploring Random Tree (RRT) and Bidirectional Rapidly-exploring Random Tree (BiRRT) were implemented for drone path planning. Our design and analysis of path planning algorithms based on RRT and BiRRT is presented. We tried to enhance the computation capability by varying the goal bias which minimizes the time to find a collision free path to the destination. Experimental results are discussed and compared. Other important issues and recommendations for future research are also discussed.